Cervical Necrotizing Fasciitis in Adults: A Life-Threatening Emergency in Oral and Maxillofacial Surgery - Patricia de Leyva; Paula Dios-Díez; Cristina Cárdenas-Serres; Ángela Bueno-de Vicente; Álvaro Ranz-Colio; Eduardo Sánchez-Jáuregui; Fernando Almeida-Parra; Julio Acero-Sanz (Surgeries, 2024)
Necrotizing fasciitis (NF) is a life-threatening soft-tissue infection affecting the deep fascia and subcutaneous tissue. It is characterized by a fulminant course and high mortality rates. NF of the head and neck is very rare, with most cases being odontogenic in origin. The purpose of this study is to comprehensively review the most important features of cervical necrotizing fasciitis (CNF) in adults and add our experience in the management of this entity. The most common isolated organisms are Streptococcus spp. and Staphylococcus spp. If the infection progresses to descending mediastinitis, the prognosis becomes very poor. Since the initial clinical features can be similar to those of a non-necrotizing deep cervical infection, a high degree of suspicion is critical for an early diagnosis. A computed tomography scan is essential for the diagnosis and to define the extent of the infection/rule out descending mediastinitis. Early and aggressive surgical debridement of all compromised tissue and antibiotic therapy and fluid resuscitation are essential and should not wait for bacterial culture results. Despite prompt and adequate treatment, the mortality of CNF can be as high as 35%.